Platelet Aggregation Induced by Basement Membranes - Hugues, J; Mahieu, P (Thrombosis and Haemostasis, 1970)
Purified suspension of basement membranes have been prepared from renal tubules or glomerules.Platelets adhere to fragments of basement membranes. With turbidimetric technique platelets from PRP were aggregated, without delay, by suspension of basement membranes especially from tubular origin. The kinetic of this phenomenon was similar to the one of platelet aggregation induced by a suspension of purified collagen fibers. Similarities and differences between the action of tubular membranes and that of collagen on platelets are discussed.A soluble factor with platelet aggregating effect was found in the supernatant of suspension of basement membranes. The chemical nature of this new platelet aggregating is still unknown. We may de bealing with the degradation product of a collagenlike protein.It is concluded that basement membranes are able to produce strong platelet aggregation. This phenomenon might possibly play a significant role in the early stages of intravascular thrombosis.